Nursing students’ attitudes on caring for people living with HIV/AIDS. A European Multicentre Study: Nursing students’ attitudes and HIV - Bonacaro, Antonio; Stroumpouki , Theodora; Triglia, Carmela; Vizilio , Emanuele; Stavropoulou , Areti; Papageorgiou, Dimitrios; Rubbi , Ivan (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Caring for people with HIV/AIDS is a challenging issue for nursing students, involving sometimes misconceptions due to different cultural, political and religious views. The aim of this project was to investigate nursing students’ attitudes on caring for people with HIV/AIDS. Methods: A convenient sample of undergraduate nursing students enrolled in four European universities was recruited. Data were collected by administering the AIDS Attitude Scale (AAS). Statistical analysis included the ANOVA test, the t–test for independent variables, and the Kruskal-Wallis test with a confidence level P <0.05. Results: The sample consisted of 594 students of which 162 (27.3%) were English, 246 (41.4%) Italian and 186 (31.3%) Greek. Study findings demonstrated that students’ attitudes toward HIV/AIDS patients were relatively positive, although the majority of them indicated fear of contracting HIV through clinical practice. Nursing students’ positive feelings for HIV/AIDS patients were also correlated with the strong willingness to take care of them. Conclusions: Despite being exposed to different teaching and learning experiences, a significant part of the participants believe that HIV/AIDS make nursing a high-risk profession. Furthermore, students’ misconceptions are not limited to clinical practice areas as they expressed concerns in sending their children in a class along with a child affected by AIDS and/or in dining in a restaurant where a chef affected by AIDS works. Students are in general well-disposed towards this patients’ population but there is still stigma associated with this condition. A new teaching and learning approach may help redefining students’ attitudes and in limiting the negative impact of misconceptions on the quality of nursing care. Further investigation in this area would help in shading light on the reasons why students are still biased in approaching AIDS/HIV patients. The use of a qualitative approach based on semi-structured interviews and/or focus group would be recommended.